Про торичні вузли T(n, 4) і поліноми Чебишова - Pavlyuk, A.M. (Publishing house "Academperiodika", 2012)
The Alexander polynomials ∆n,3(t) and ∆n,4(t) are presented as a sum of the Alexander polynomials ∆k,2(t). These polynomials are also expressed in the form of a sum of Chebyshev polynomials of the second kind. These expansions allow one to introduce the "coordinates" in corresponding bases, which are proposed to be the numerical invariants characterizing links and knots.